Recognizing the threshold magnetic anisotropy for inclination shallowing: implications for correcting inclination errors of sedimentary rocks - Li, Yong-Xiang; Wang, Shipeng; Fu, Shaoying; Jiao, Wenjun (Frontiers in Earth Science, 2014)
Post-depositional compaction is an integral part of sedimentary rock formation and thus has been reasonably deemed as a major culprit for the long-recognized inclination-shallowing problem in sedimentary rocks. Although theoretical treatment elegantly envisions magnetic anisotropy (or oblate fabrics) to correspond to the degree of compaction and the magnitude of inclination flattening, such correspondence has rarely been seen in nature quantitavely, which leaves the possibility of misidentification and/or over-correction for inclination shallowing using magnetic anisotropy. This is because the extent to which oblate magnetic fabrics are developed strongly enough for inclination to start becoming shallow is not yet known. Here, we present sedimentary paleomagnetic data from two ~6 m long gravity cores GHE24L and GHE27L from the northern slope of the South China Sea to examine the down-core changes in magnetic anisotropy and inclinations, and to explore the possible connection between the two parameters. The results show that oblate fabrics are dominantly developed at depths >~2m and the degree of anisotropy displays an overall gradual increase with depth. Inclination shallowing occurs in the > 5m segment of the relatively distal core GHE27L and the amount of shallowing largely correlates with the degree of anisotropy, suggesting a causal relation between the development of magnetic anisotropy and the degree of inclination shallowing. Examination of down-core changes in inclination and magnetic anisotropy suggests that a threshold anisotropy of PAMS~1.04 and PAAR~1.10 exists for inclination shallowing in the cores. For PAAR<1.10, over-correction is mostly negligible, but can amount >10° if particle anisotropy is <1.4. This study provides strong field evidence that complements and substantiates the theoretical model and suggests that the threshold anisotropy can be used as a first-order criterion to identify inclination errors of some sedimentary rocks.